Buddhist Knowledge in Social Media - ขนฺติโก พระครูขันติวโรภาส (Journal of Educational Review Faculty of Education in MCU, 2018)
Social media linked to one another reasonably. In Life of the Buddha and of other disciples, it revealed that the search for knowledge, the process in searching for knowledge and learning method were conformed to knowledge in the social media. Creative thinking, problem solutions, leadership in the pursuit of knowledge and the knowledge to career love did not contradict the Buddhist principles and legal principles. That Knowledge was called the middle way in Buddhism. The knowledge in social media was temporary because the knowledge was emerged all the time and was to satisfy human desires.